ЕЛІТА ТА РОЗПОДІЛ СУСПІЛЬНОГО КАПІТАЛУ (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the consideration of 2 main approaches to the determination of elite: power (elite as the ruling group) and value (elite as the best representatives of society). Author comes to the conclusion: there is no great difference between these approaches, because they describe different types of the elite.